Comprehensive treatment of strut-and-tie approach across concrete deep beams reinforced with different systems - Alqarni, Ali H. (My University, 2025)
This dissertation investigates the nonlinear behavior of reinforced concrete deep beams, combining experimental and analytical methodologies to assess the influence of material and geometric variables. The study introduces a matrix truss analysis method for predicting load-deflection behavior at critical stages for different reinforcement materials; conventional steel bars and Glass Fiber Reinforced Polymer (GFRP) bars. The method employs the strut and tie model to enhance the accuracy of nodal displacements and load predictions without postulating the nonlinear strain profile. Further, an experimental evaluation explores the effects of concrete strength and steel reinforcement ratios under monotonic loading, highlighting the impact of shear span-to-depth ratios on beam performance. Finally, a parametric analysis employing the strut and tie method, applied to steel-reinforced concrete deep beams, clarifies the relationships among various structural parameters, revealing strong correlations between the characteristics of deep beams and prediction outcomes. This enhances our understanding of deep beam mechanics and contributes to safer, more effective and accurate structural designs
Keywords: Deep beams; Reinforced concrete; Strut and tie method; GFRP; Experiments; Sensitivity analysis